How Post-Soviet Secessions Appear: Factors Contributing to and Hindering Exit - A. A. Tokarev (Международная аналитика)
The article deals with “complex” cases of territorial development after the collapse of the USSR: secession, autonomization, gray zones of statehood in all post-Soviet republics. Taking into account both realistic and constructivist grounds of secession, the author lists the main factors (geographical, historical, political, sociological, cultural, linguistic, military) that aﬀect the processes of autonomy and the withdrawal of territorial polities from the parent states, postulating that none of them is repeated in all 20 cases studied. This means that no factor is determinative, although Western sources often refer to Russian patronage in the post-Soviet space as such. The most popular factors are the functioning of the state -the segment within which the secession is being formed, and the presence of a political organization among the separatists (17 cases out of 20).